Development of a factor-criterion model for evaluating research competence of future managers - Bachiеva, L. (Problems of Engineer-Pedagogical Education, 2020)
The increasing dynamism and diversification of management processes have created conditions for the emergence and development of a research management function. The analysis of relevant scientific works and personal experience allowed formulating the definition of "managerial research competence" and revealing its components. Thus, cognitive, operational-technological, active, personal and reflexive components of the research competence of future managers were defined. Assessing the level of competence development requires objective and qualitative tools. Based on theoretical provisions of qualimetry, an algorithm for the development of qualimetric tools was developed to measure the degree of research competence, which consists of five steps, namely: defining the essence of the term "factor-criterion model of managerial research competence"; substantiating the components of the factor-criterion model; presenting the identified factors and criteria; describing the method for determining the weighting coefficients for each of the factors and criteria; drawing up the factor-criterion model. Recommendations are given for the implementation of each of the steps necessary to implement the presented algorithm. In particular, the most difficult stage of the work is the application of the peer-review method. In order to optimize its application, an algorithm for implementing the method of expert evaluation in the process of determining the weight of factors and criteria for evaluating research competence is presented. The algorithm contains the following steps of implementation: defining a group of experts; establishing the competence of each expert; determining the optimal number of experts; final formation of the expert group. Thus, a factor-criterion model for evaluating the research competence of future managers was developed, based on the structure of research competence of future managers, factors and their criteria, weighting coefficients of factors and their criteria. The developed model can be applied in higher education institutions to assess research competence of future managers.